Comics: An Alternative Visualization Tool for Post-Rationalist Architecture - Wannathepsakul, Natre (Journal of Architectural/Planning Research and Studies (JARS), 2020)
Representational tools are never just a neutral vehicle of communication. The postwar critique of modernist architecture and the emergence of certain strands of post-rationalist architecture that prioritized the aesthetic, socio-cultural and sensorial dimensions were accompanied by attempts by architects such as Alison and Peter Smithson and Nigel Coates to come up with alternative methods of architectural visualization that would correspond to their particular interests and directions. This paper traces their developments and then proposes the medium of comics as a way to document the specificity of the socio-cultural makeup of a place and to represent architecture that focuses on human perception and sensorial experiences. The paper focuses on three properties of comics: its sequential nature through the use of panels allowing for the element of time and therefore storytelling, the portrayal of characters and the graphical techniques that strive to render non-visual experiences visually. The architectural comics presented in this paper suggest that the medium has been employed and experimented with by contemporary architects, though works of a more poetical nature are still regarded as hobbies and beyond the boundary of professional practice. While narrative elements such as paneling and characterization have been handled effectively if somewhat straightforwardly, certain distinctive graphical techniques of comics remain little explored.